ANALYSING THE IMPACT OF UNEMPLOYMENT AND POVERTY RATES ON INDONESIA'S GROSS DOMESTIC PRODUCT USING REGRESSION - Darmadi, Eric (Journal Economics & Business Atmajaya Indonesia, 2019)
The influence between number of unemployment and number of poor population on Indonesian GDP is shown by regression analysis in Rstudio software. Transformation of regression is examined in order to equalize units between variables in which the effect of increase or decrease can be interpreted by percentage. The number of unemployment has a significant influence on the GDP with a 99% confidence level where a 1% increase in the number of unemployment will raise GDP by 1.5581%. The number of poor population has a significant influence on the GDP with a confidence level of 99.9% where an increase of 1% on poor population will reduce GDP by 3.6266%. The number of unemployment and the number of poor population simultaneously has a significant effect on the GDP with a confidence level of 100% where the dominant effect is on the poor population. The results of statistical tests show the transformation of regression between the number of unemployment and the number of poor population can illustrate its effect on the GDP up to 62.54%. The proposed policy implication based on the regression is to maintain the equilibrium between the price setting and the wage setting that provides welfare for the community so that poverty can be suppressed. Decreasing poverty will increase the consumption power of the population in which Indonesia's GDP will increase as well.